PERBEDAAN GENDER DALAM KEMAMPUAN SPASIAL DAN FAKTOR-FAKTOR YANG MUNGKIN MEMPENGARUHINYA : PERBEDAAN GENDER DALAM KEMAMPUAN SPASIAL MATEMATIS DAN FAKTOR-FAKTOR YANG MUNGKIN MEMPENGARUHINYA - Silitonga, R. H. Yanti; Ratumanan, T. G.; Telaumbanua, Esterni (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to quantitatively investigate the spatial ability differences between male and female students to provide empirical evidence. In this study, 36 high school students took the sample. Spatial ability tests are used to gather data about student spatial abilities. The data is then analyzed using a T-test to test the hypothesis. The results of the study showed that there were significant differences between the spatial abilities of male and female students, and in general or as per gender, the student's space capacity was still low. Factors that may influence significant gender differences are biological and social-cultural, while the student's spatial abilities are still low because the students are not accustomed to getting training on issues related to space abilities. The use of learning media for student spatial abilities is not optimal.